An Assessment of School Clinic Services: Administrative Challenges and their Effectiveness in Promoting Student Health and Academic Support - Villaganas, Genalyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the effectiveness of school clinic services and the administrative challenges encountered in their delivery at Malbug National High School. The study was anchored on Bronfenbrenner’s Ecological Systems Theory, Imogene M. King’s Theory of Goal Attainment, and Maslow’s Hierarchy of Needs, which emphasize the importance of environmental support, collaborative healthcare, and health and safety in student development. A descriptive-survey research design was employed involving forty (40) student respondents selected through convenience sampling. Data were gathered using a researcher-developed questionnaire and analyzed using frequency count, percentage, weighted mean, and Pearson Product-Moment Correlation Coefficient (Pearson r). The findings revealed that the respondents were predominantly female, with equal representation from the 12–15 and 16–18 age groups, and most were Grade 12 students. School clinic services, including first aid and emergency care, medical consultation and referral, health assessment and monitoring, and the provision of medicines and supplies, were rated highly effective. Likewise, accessibility, adequacy of facilities and equipment, competence of clinic personnel, and responsiveness to students’ health needs were assessed as very effective. Despite these positive assessments, respondents identified serious administrative challenges related to insufficient medicines, inadequate facilities and equipment, limited clinic services, lack of health personnel, and inadequate funding. The study further found a significant positive relationship between the challenges encountered and the effectiveness of school clinic services. The study concludes that school clinic services play a vital role in supporting student health and academic success but require continuous improvement through enhanced resources, adequate staffing, sufficient funding, and stronger collaboration with stakeholders. The study supports Sustainable Development Goal (SDG) 3: Good Health and Well-Being and SDG 4: Quality Education by highlighting the importance of accessible school health services in promoting student wellness and learning outcomes. Its sustainability contribution lies in providing evidence that may guide improvements in school health programs, resource allocation, and service delivery, thereby fostering a healthier and more supportive learning environment.